Little Louie the baby bloomer - Kraus, Robert, 1925-; Aruego, Jose; Dewey, Ariane (New York : HarperCollins, 1998)
Leo the tiger worries and wonders why his little brother can't do anything right, but his parents encourage Leo to be patient.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
2.2
K-3
360L
Keywords: Tigers -- Fiction; Toddlers -- Fiction; Brothers -- Fiction; Tigers -- Fiction; Infants -- Fiction; Brothers -- Fiction; Tigers -- Fiction; Toddlers -- Fiction; Brothers -- Fiction